Contribution of sustainable street vending to municipal solid waste management in Tanzania: A case of Morogoro municipality - Apolo, Didas (Mzumbe University, 2023)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Masters of Science in Environmental Management (MSc. EM) of Mzumbe University